Xenophon the Socratic Prince : The Argument of the Anabasis of Cyrus - Buzzetti, Eric.; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
An interpretation of Xenophon's Anabasis of Cyrus, paralleling the text to Machiavelli's The Prince, and focusing on the question: How did the Socratic education help Xenophon reconcile morality with effectiveness, the noble with the good, as a ruler?.
Keywords: Science